Multidrug resistance in Helicobacter pylori infection - Dascălu, Raluca Ioana; Bolocan, Alexandra; Păduaru, Dan Nicolae; Constantinescu, Alexandru; Mitache, Magda Mihaela; Stoica, Anca Daniela; Andronic, Octavian (Frontiers in Microbiology, 2023)
elicobacter pylori (Hp), a well-known human pathogen causes one of the most common chronic bacterial infections, playing an important role in the emergence of chronic progressive gastric inflammation and a variety of gastro-intestinal diseases. The prevalence of Hp infection varies worldwide, indirectly proportional to the socio-economic status, especially during childhood. The response to the eradication therapy significantly depends on the antibiotic resistance specific to each geographical region, thus, currently, given the increasing prevalence of antimicrobial resistance (especially to clarithromycin, metronidazole and levofloxacin), successful treatment for Hp eradication has become a real challenge and a critical issue. The most incriminated factors associated with the multidrug resistance (MDR) in Hp proved to be the overuse or the improper use of antibiotics, poor medication adherence and bacterial related factors including efflux pumps, mutations and biofilms. Up to 30% of first-line therapy fails due to patient’s compliance, high gastric acidity or high bacteremia levels. Hence, it is of great importance to consider new eradication regimens such as vonoprazan-containing triple therapies, quintuple therapies, high-dose dual therapies, and standard triple therapies with probiotics, requiring further studies and thorough assessment. Strain susceptibility testing is also necessary for an optimal approach.